Precautionary principle under the cartagena protocol on transboundary movement of LMOs - Ansari, Abdul Haseeb; Wartini, Sri (American-Eurasian Network for Scientific Information, 2013)
The Cartagena Protocol, made under the Convention on Biological Diversity, aims at protecting the ‘human, animal and plant life and health’ by prescribing a high standard of precautionary principle. This has to be based on risk assessment. Thus, the importing countries of GMOs/LMOs have the right to invoke the precautionary principle provisions enshrined in the Cartagena Protocol and the exporting countries have to provide required relevant information. This is working well. However, there are certain controversial legal and ethical aspects that require to be revisited and have to be amicably settled so that there could be wider acceptability of the precautionary principle. It has been observed that a large number of states prefer international trade in GMOs/LMOs over protection of human health and the environment, some countries for a short-term economic gain ignore this aspect. Likewise, some scientists for the sake of name and fame or quick hauling of money, wish to introduce GMOs produced by them. The paper thoroughly discusses these and offers certain amicable solutions to them.